MINISTRY OF JUSTICE OF THE UKRAINIAN STATE DURING THE PERIOD OF PAVLO SKOROPADSKY'S HETMANSHIP (1918) IN UKRAINIAN HISTORIOGRAPHY - SHCHEBETIUK, Nataliia; TSYBULIN, Taras (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the study is to elucidate the areas of research into the activities of the Ministry of Judicial Affairs (from April 29, 1918 – the Ministry of Justice) of the Ukrainian State during the period of Pavlo Skoropadsky's Hetmanship in Ukrainian historiography. The research methodology is based on the principles of historicism, scientific objectivity, systematicity, and comprehensiveness. In the article general scientific (analysis, synthesis, generalization) and special historical methods (comparative historical and bibliometric) have been used. Scientific Novelty. Modern Ukrainian historiography has been analyzed, the main problems of studying the activities of the Ministry of Judicial Affairs (Justice) during the time of Pavlo Skoropadsky have been outlined. Conclusions. The study of state-building processes within the Ukrainian State during Pavlo Skoropadsky's Hetmanship begins with the completion of the national liberation struggles, in particular, during the interwar period in the emigrant circles, the first memoirs and journalistic essays of the former UNR figures, supporters of the Hetman's regime, were published. The long history of research on these issues in emigration, in the Soviet historical and legal science became the foundation for further research in Ukrainian science. Many publications by O. Reient, V. Verstiuk, V. Soldatenko and the others focus on covering the change of power and Pavlo Skoropadsky's coming to power, qualifying the essence of the Hetmanate, and analyzing his state position. Biographical sketches and a comprehensive analysis of the Hetman's activities were carried out by H. Papakin and R. Pyrih. More narrow issues of the state apparatus development during the period of 1917 – 1920, and in particular the Ukrainian State during P. Skoropadsky's Hetmanship, various government branches formation, in particular the judicial system, were covered by the following historians and lawyers: B. Tyshchyk, O. Vivcharenko and N. Leshkovych, O. Myronenko, R. Pyrih, H. Papakin, O. Tymoshchuk, and I. Usenko. Key words: Ministry of Justice, Pavlo Skoropadsky, Ukrainian National Democratic Revolution, Ukrainian state, historiography.